Critical Review and Consensus Statement for Neural Monitoring in Otolaryngologic Head, Neck, and Endocrine Surgery. (18th May 2021) - Scharpf, Joseph; Liu, Jeffrey C.; Sinclair, Catherine; Singer, Michael; Liddy, Whitney; Orloff, Lisa; Steward, David; Bonilla Velez, Juliana; Randolph, Gregory W.
Abstract : Background: Enhancing patient outcomes in an array of surgical procedures in the head and neck requires the maintenance of complex regional functions through the protection of cranial nerve integrity. This review and consensus statement cover the scope of cranial nerve monitoring of all cranial nerves that are of practical importance in head, neck, and endocrine surgery except for cranial nerves VII and VIII within the temporal bone. Complete and applied understanding of neurophysiologic principles facilitates the surgeon's ability to monitor the at‐risk nerve. Methods: The American Academy of Otolaryngology–Head and Neck Surgery (AAO‐HNS) identified the need for a consensus statement on cranial nerve monitoring. An AAO‐HNS task force was created through soliciting experts on the subject. Relevant domains were identified, including residency education, neurophysiology, application, and various techniques for monitoring pertinent cranial nerves. A document was generated to incorporate and consolidate these domains. The panel used a modified Delphi method for consensus generation. Results: Consensus was achieved in the domains of education needs and anesthesia considerations, as well as setup, troubleshooting, and documentation. Specific cranial nerve monitoring was evaluated and reached consensus for all cranial nerves in statement 4 with the exception of the spinal accessory nerve. Although the spinal accessory nerve's value can never be marginalized, the task force did not feel that the existing literature was as robust to support a recommendation of routine monitoring of this nerve. In contrast, there is robust supporting literature cited and consensus for routine monitoring in certain procedures, such as thyroid surgery, to optimize patient outcomes. Conclusions: The AAO‐HNS Cranial Nerve Monitoring Task Force has provided a state‐of‐the‐art review in neural monitoring in otolaryngologic head, neck, and endocrine surgery. The evidence‐based review was complemented by consensus statements utilizing a modified Delphi method to prioritize key statements to enhance patient outcomes in an array of surgical procedures in the head and neck. A precise definition of what actually constitutes intraoperative nerve monitoring and its benefits have been provided.